2016
DOI: 10.1158/1940-6207.capr-16-0038
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Urine and Cervical Samples for HPV DNA Detection and Typing in Young Women in Colombia

Abstract: Urine sampling for HPV DNA detection has been proposed as an effective method for monitoring the impact of HPV vaccination programs; however, conflicting results have been reported. The goal of this study was to evaluate the performance of optimized urine HPV DNA testing in women aged 19 to 25 years. Optimization process included the use of first void urine, immediate mixing of urine with DNA preservative, and the concentration of all HPV DNA, including cell-free DNA fragments. Urine and cervical samples were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 45 publications
5
25
0
1
Order By: Relevance
“…Furthermore, whereas previous studies have almost all reported a moderate under detection of HPV in urine compared to paired cervical cell samples [1], we report that the combination of a strict protocol for urine sampling and a highly sensitive HPV detection assay (E7-MPG), resulted in detection of more HPV in urine than in cervical cells. This finding matches that of a recent study in Colombia using a similar urine sampling procedure and HPV assay (PR = 1.08 for any HPV) [17]. Neither in the present, nor the Colombian study, was there any clear evidence that HPV type distribution varied between the two sample types, suggesting that urine is broadly representative of the types collected at the cervix, at least with respect to the 21 types evaluated by both E7-MPG and GP5+/6+.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, whereas previous studies have almost all reported a moderate under detection of HPV in urine compared to paired cervical cell samples [1], we report that the combination of a strict protocol for urine sampling and a highly sensitive HPV detection assay (E7-MPG), resulted in detection of more HPV in urine than in cervical cells. This finding matches that of a recent study in Colombia using a similar urine sampling procedure and HPV assay (PR = 1.08 for any HPV) [17]. Neither in the present, nor the Colombian study, was there any clear evidence that HPV type distribution varied between the two sample types, suggesting that urine is broadly representative of the types collected at the cervix, at least with respect to the 21 types evaluated by both E7-MPG and GP5+/6+.…”
Section: Discussionsupporting
confidence: 91%
“…When urine HPV analyses were compared to HPV tests obtained from cervical material, the sensitivity ranged from 53-100% and the specificity from 67% to 100% (2,9). Our urine sample results regarding sensitivity and specificity values are similar to an earlier study comparing HPV testing in urine specimen to cervical samples (10).…”
Section: Discussionsupporting
confidence: 78%
“…The results show that HPV infection is very common among sexually active young women. A total of 60.3% of participants were HPV positive, which confirms that HPV is highly endemic in our population (20). This prevalence is greater to the prevalence reported in other regions like Brazil, United States, and Europe, which has ranged from 25% to 49.9% among sexually active women (15,(21)(22)(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 70%
“…The high prevalence of this genotype has been reported also in others populations including Eastern Africa, Japan, and Eastern Asia among women with normal cytology and even in women with abnormal cytology. However, previous studies in Colombia have shown HPV 58 as the second most prevalent type in young women in cervical samples, but in urine samples, HPV 52 was the second type (20). These differences might be explained by differences in the method used to detect HPV DNA.…”
Section: Discussionmentioning
confidence: 83%